Excessive dietary lipid intake provokes an acquired form of lysosomal lipid storage disease in the kidney - Rampanelli, Elena; Ochodnicky, Peter; Vissers, Johannes PC; Butter, Loes M; Claessen, Nike; Calcagni, Alessia; Kors, Lotte; Gethings, Lee A; Bakker, Stephan JL; de Borst, Martin H; Navis, Gerjan J; Liebisch, Gerhard; et al. (The Journal of pathology, 2018)
Obesity and dyslipidaemia are features of the metabolic syndrome and risk factors for chronic kidney disease. The cellular mechanisms connecting metabolic syndrome with chronic kidney disease onset and progression remain largely unclear. We show that proximal tubular epithelium is a target site for lipid deposition upon overnutrition with a cholesterol‐rich Western‐type diet. Affected proximal tubule epithelial cells displayed giant vacuoles of lysosomal or autophagosomal origin, harbouring oxidised lipoproteins and concentric membrane layer structures (multilamellar bodies), reminiscent of lysosomal storage diseases. Additionally, lipidomic analysis revealed renal deposition of cholesterol and phospholipids, including lysosomal phospholipids. Proteomic profiles of renal multilamellar bodies were distinct from those of epidermis or lung multilamellar bodies and of cytoplasmic lipid droplets. Tubular multilamellar bodies were observed in kidney biopsies of obese hypercholesterolaemic patients, and the concentration of the phospholipidosis marker di‐docosahexaenoyl (22:6)‐bis(monoacylglycerol) phosphate was doubled in urine from individuals with metabolic syndrome and chronic kidney disease. The enrichment of proximal tubule epithelial cells with phospholipids and multilamellar bodies was accompanied by enhanced inflammation, fibrosis, tubular damage markers, and higher urinary electrolyte content. Concomitantly to the intralysosomal lipid storage, a renal transcriptional response was initiated to enhance lysosomal degradation and lipid synthesis. In cultured proximal tubule epithelial cells, inhibition of cholesterol efflux transport or oxysterol treatment induced effects very similar to the in vivo situation, such as multilamellar body and phospholipid amassing, and induction of damage, inflammatory, fibrotic, and lipogenic molecules. The onset of phospholipidosis in proximal tubule epithelial cells is a novel pathological trait in metabolic syndrome‐related chronic kidney disease, and emphasises the importance of healthy lysosomes and nutrition for kidney well‐being. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.